Electronic entropy change in Ni-doped FeRh. (June 2019) - Pérez, N.; Chirkova, A.; Skokov, K.P.; Woodcock, T.G.; Gutfleisch, O.; Baranov, N.V.; Nielsch, K.; Schierning, G.
Abstract: The net entropy change corresponding to the free charge carriers in a Ni-doped FeRh bulk polycrystal was experimentally evaluated in a single sample using low-temperature heat capacity experiments with applied magnetic field and using Seebeck effect and Hall coefficient measurements at high temperatures across the first-order phase transition. From the heat capacity data, a value for the electronic entropy change Δ S e l ≈ 8.9 J kg −1 K −1 was extracted. The analysis of the Seebeck coefficient allows tracing the change of the electronic entropy jump with applied magnetic field directly across the transition. The difference in electronic entropy contribution obtained is as high as 10% from 0.1 to 6 T. Graphical abstract: Image 1 Highlights: Metamagnetic transition in FeRh alloys. Electronic entropy change. Single Sample Study. Low Temperature Heat Capacity. Seebeck effect.